Case Report: Myelin Oligodendrocyte Glycoprotein Antibody-Associated Disorder Masquerading as Multiple Sclerosis: An Under-Recognized Entity? - Zheng, Yang; Cai, Meng-Ting; Li, Er-Chuang; Fang, Wei; Shen, Chun-Hong; Zhang, Yin-Xi (Frontiers in Immunology, 2021)
Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) covers a wide spectrum of manifestations and is defined by the presence of MOG seropositivity. However, in a proportion of patients, there may be an overlap in some of the clinical and radiological manifestations between MOGAD and multiple sclerosis (MS). Being wary of this entity is critical to ensure appropriate therapy. Herein, we present a case with recurrent episodes of short-segment myelitis typical for multiple sclerosis, but later diagnosed as MOGAD by MOG antibody seropositivity. This case, along with previous reports, highlights an increasingly-recognized subgroup in MOGAD with initial clinical phenotypes suggestive of MS, but later showing a disease course and therapeutic response compatible with MOGAD. Given the potential overlap of some clinical phenotypes in patients with MS and those with MOGAD, we recommend MOG antibody testing in all patients with recurrent short-segment myelitis, conus medullaris involvement, and those who demonstrated steroid dependence.